Soroprevalência para arboviroses humanas de interesse em saúde pública como marcador de impacto ambiental em comunidades ribeirinhas que vivem sob a influência da usina hidrelétrica de Tucuruí-Pará - BRITO, Mioni Thieli Figueiredo Magalhães de (Universidade Federal do Pará, 2013)
The arboviruses are a major public health problem in Brazil, especially in the Amazon for its ability to cause epidemics with considerable rates of morbidity and mortality in both humans and animals. Four, Virus dengue (VDEN), Virus yellow fever (VYF), Virus Mayaro (VMAY) and Virus Oropouche (VORO) has special relevance for the region, particularly in those environments where environmental impacts are imminent. Studies on the prevalence of antibodies to arboviruses in this region are limited. This study aimed to estimate the prevalence of antibodies to arboviruses of the major public health concern in the communities that live under the influence of the Tucuruí dam in the state of Pará. The study was observational, cross-sectional analytical study carried out in individuals of both sexes, aged over 18, resident at the left and right margin of the lake Tucuruí power plant and from the RDS and Alcobaça Pucurui-ararão. The collection of blood samples and filling in the questionnaire were performed at two different times, flood and ebb of the lake. All samples were analyzed by the Evandro Chagas Institute where they were tested with hemagglutination inhibition for detection of antibodies against 19 types of Arboviruses and MAC-ELISA test for detection of IgM antibodies. Data analysis was descriptive and analytical, are used to calculate odds ratio with confidence interval 95% to determine the association between the study variables and chi-square or Fisher exact test to verify the significance statistical relationships between the variables of the study with an alpha level of 0.05. In all, 635 individuals were studied and the antibodies to arboviruses was significantly associated with sociodemographic characteristics of individuals such as sex, ossupation and residence time in study area. No association was found between the presence of antibodies arboviral and other traits.